(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The use of antioxidants is an effective approach to prevent symptoms related to photo-induced aging of the skin. The aim of this research work was to formulate and evaluate a polyherbal antioxidant face cream using the ethanol extracts of Tetracarpidium conophorum and Ocimum gratissimum. The ethanol extract of the herbs was incorporated at varying concentrations into six different emulsion bases. Antioxidant activity of the formulations was assessed using 2,2-diphenyl-1-picrylhydrazyl method. The formulations were evaluated for pH, viscosity, spreadability and microbial content. Accelerated stability tests were performed on all the formulations to assess stability at varying storage conditions. All the formulations showed good spreadability, good consistency, homogeneity, appearance, pH and no phase separation occurred. Non-Newtonian pseudo-plastic flow influenced by increased shear was experienced by all the formulations. Concentration dependent antioxidant activity was observed with FC2 and FC4 showing the highest antioxidant activity with IC50 value of 80.1 and 83.2 μg/ml, respectively. The polyherbal antioxidant preparation containing extracts of T. conophorum and O. gratissimum shown to exhibit excellent antioxidant properties. It can serve to protect the skin from reactive oxygen species created by UV radiation and environmental toxin, thus protecting the skin from photo aging. Dhaka Univ. J. Pharm. Sci. 17(2): 213-219, 2018 (December)